Access to Higher Education for Persons with Disabilities: A Document Study and Thematic Analysis of Structural Barriers and Reasonable Accommodations - Neneng Tati Sumiati; Ajang Sopandi; Asep Taufik Muharram; Cindy Rahayu; Siti Ummi Masruroh; Gina Sagita (Mimbar Agama Budaya, 2025)
Access to higher education for people with disabilities still faces structural and multidimensional barriers, as access does not stop at student admission but encompasses academic access, support services, information, and campus social participation. This study aims to map the main barriers and directions for improving higher education access policies for people with disabilities by referring to the non-discrimination and reasonable accommodation mandates in the CRPD. The method used is qualitative research based on document studies through thematic analysis of normative documents and authoritative reports (CRPD, OECD), as well as evidence of national and cross-country educational inequality (UNICEF Indonesia, World Bank). The results show that access to higher education is influenced by (1) uneven support and accommodation across institutions, which often makes meeting needs dependent on campus capacity; and (2) pipeline issues resulting from inequalities at previous levels, marked by low participation and graduation rates for groups with disabilities, thus narrowing opportunities to advance to higher education. These findings emphasize the need for an integrated access policy through minimum standardization of academic accommodations, strengthening disability service units, simplifying support procedures, and transition strategies from secondary education to higher education so that equal access can be achieved sustainably.